A very low speech model based on frequency selection-GA approach. (2018) - Mitiche, Lahcène; Adamou-Mitiche, Amel Baha Houda
Using a new model order reduction based on frequency selection and optimal genetic algorithm, a second order speech model is calculated. In our algorithm, the modeling process starts with a full order classical all poles model obtained by Burg method. The full order model AR is reduced using the proposed approach based on the genetic algorithms and the original speech production system dominant frequencies. The model reduction yields to a ARMA second order model which interestingly preserves the key properties of the original full order model in the time and frequency domains. To illustrate the performance and the effectiveness of the proposed approach, some computer simulations are conducted on some practical speech segments. To show the novelty of our approach, a comparative study with an approximant given by the robust SVD-Schur technique is presented.